Adab Guru dan Murid: Studi Komparatif Pemikiran Imam Ibnu Jama'ah, KH. Hasyim Asy'ari, dan Imam Al-Jarnuzi - Cucu Cahyati; Nopianti Saadah (CV. AFDIFAL MAJU BERKAH, 2026)
Understanding the concept of teacher-student etiquette in the Islamic tradition cannot be separated from the historical and socio-scholarly backgrounds of each figure. From an Islamic perspective, etiquette is not merely a matter of manners, but rather the spiritual foundation of scholarship. Classical scholars emphasize that etiquette is a prerequisite for knowledge to bring blessings rather than harm. This article conducts an in-depth comparative analysis of the concept of teacher-student etiquette from the perspectives of three prominent scholars: Imam al-Zarnuji, Imam Ibn Jama’ah, and K.H. Hasyim Asy’ari, with a focus on the close connection between their educational philosophies and the historical and socio-intellectual contexts of their respective eras. The objective of this study is to elucidate how the dynamics of the educational environment—ranging from the personal Halaqah system, formal madrasah institutions, to Pesantren under colonial pressure—gave rise to distinct characteristics in the focus and scope of Adab. This study used Library Research approach. The Data were analyzed descriptively and comparatively. The findings of this study were : al-Zarnuji’s emphasis on individual student behavior, Ibn Jama‘ah’s focus on the balance of rights and obligations within an institutional context, and Hasyim Asy‘ari’s most systematic and community-oriented elaboration. The implications for modern Indonesian education are that the revitalization of Adab involves strengthening ethical codes, integrating humanistic and spiritual values, and applying gradual and interactive methods. The main commonalities among the three include sincere intention, the duty to honor and obey the teacher, patience and gentleness, not overburdening students, repetition of material, moral supervision, teacher fairness, and student patience toward the teacher. This research is beneficial theoretically, practically, and culturally by bridging universal Islamic traditions and the local wisdom of the Nusantara, making the works of these scholars a highly relevant legacy for the ethical challenges of education today.